2021
DOI: 10.1007/s00330-021-08165-5
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of wrist anatomy—a comparison between 7T and 3T MRI

Abstract: Objective Injuries to the wrist are, due to its small size and complex anatomical structures, difficult to assess by MR, and surgical interventions such as diagnostic arthroscopy are often necessary. Therefore, improved visualization using non-invasive methods could be of clinical value. As a first step of improvement, the purpose of this study was to evaluate visualization of anatomical structures at 7T compared with 3T MR. Methods Eighteen healthy volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Studies performing compositional MRI techniques at the wrist are rare, which may be related to difficulties in image acquisition and quantification due to the small size of the anatomic structures at the wrist [ 1 ]. Götestrand et al [ 12 ] reported a superior depiction of several anatomical structures, including the articular cartilage and different parts of the TFCC, for 7 T compared with 3 T in a small sample of healthy volunteers, emphasizing the potential of wrist imaging at ultra-high-field MRI [ 23 ]. We recently confirmed these results for cartilage imaging by comparing the image quality between 3- and 7-T MRI in a multi-reader assessment of the current study cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performing compositional MRI techniques at the wrist are rare, which may be related to difficulties in image acquisition and quantification due to the small size of the anatomic structures at the wrist [ 1 ]. Götestrand et al [ 12 ] reported a superior depiction of several anatomical structures, including the articular cartilage and different parts of the TFCC, for 7 T compared with 3 T in a small sample of healthy volunteers, emphasizing the potential of wrist imaging at ultra-high-field MRI [ 23 ]. We recently confirmed these results for cartilage imaging by comparing the image quality between 3- and 7-T MRI in a multi-reader assessment of the current study cohort.…”
Section: Discussionmentioning
confidence: 99%
“…This is of interest for the hand and wrist due to the small size of the anatomic structures. While these investigations mainly centered on data from healthy volunteers, without specific emphasis on nerve imaging, comparative studies across various field strengths demonstrate that 7T MRI allows the accurate delineation of nerves, Pacinian corpuscles, ligaments, and vessels, thereby promising an improved diagnosis of pathological conditions [ 10 , 13 ]. Correlation studies between anatomical findings and MRI abnormalities conducted on cadaveric extremities underscore a robust alignment between images and histological observations [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mavrogenis et al demonstrated that employing bone models derived from CT data and computer-assisted navigation systems has been proven to be an effective technique of surgical assistance [ 6 ]. A 3D visualization of the wrist bones is of therapeutic importance due to the tiny size and complicated anatomical features of them, which are challenging to observe in 2D images [ 7 ]. With 3D carpal models, analyses—e.g., of wrist kinematic behavior—can be directly conducted on a virtual model for therapy planning or surgery assessment [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%